ANALISIS IMPLEMENTASI ALAT PERAGA SEDERHANA UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA PEMBELAJARAN MATEMATIKA DIKELAS V SD NEGERI 02 BENGKAYANG - Meliani Gracia; Margaretha Lidya Sumarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of simple teaching aids as an effort to improve students’ understanding in mathematics learning. The background of the research is the low student comprehension of fraction material, which affects mathematics learning outcomes in fifth grade at SD Negeri 02 Bengkayang. This research used a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results show that the use of simple teaching aids such as paper cutouts, pictures, and other concrete objects helps students better understand fraction concepts. It also enables teachers to transform abstract material into more concrete explanations. In conclusion, the implementation of simple teaching aids has proven effective in enhancing students’ understanding of mathematics material, particularly on fractions in grade V. Keywords: Simple Teaching Aids, Student Understanding, Mathematics, Fractions